The Lack of the Environmental Concern in Indonesia’s Bilateral Investment Treaties - I Gusti Ngurah Parikesit Widiatedja; I Gusti Ngurah Wairocana (Faculty of Law, Hasanuddin University, 2017)
In the modern era, Bilateral Investment Treaties (BITs) are relatively effective to attract more foreign direct investment (FDI). Many countries then eagerly concluded BITs, including Indonesia. Considering the adverse impact of FDI on the environment, most countries then start putting the environmental concern in their BITs, assisting them to prevent and mitigate any adverse impact of FDI on the environment. Indonesia, however, did not follow this measure. This paper then shows the lack of the current Indonesia’s BITs in putting the environmental concern in their provisions. The fact that Indonesia has terminated some BITs becomes a right momentum to start putting the environmental concern in the updated and modified Indonesia BITs in the future. From other countries’ practices, there is evidence to suggest that BITs can and do contain provisions aimed at ameliorating environmental damage caused as a result of FDI within host countries’ territories.